Grain Yield Stability of Quality Protein Maize Genotypes across Diverse Environments of Terai and Mid Hills in Nepal - Jiban Shrestha; Mahendra Prasad Tripathi (International Journal of Agriculture System, 2014)
Maize is produced in diverse environmental conditions in Nepal. National Maize Research Program regularly tests maize genotypes for their grain yield stability in highly diverse environments. The objective of this paper is to estimate grain yield stability of quality protein maize genotypes across different environments. Two quality protein maize genotypes namely Poshilo Makai-1 and S99TLYQ-HG-B along with Farmer’s variety were tested at nine different locations of Nepal in four consecutive years before 2013 under farmer’s fields. Alpha-lattice design with two replications was used. The results of these studies revealed that S99TLYQ-HG-B was more stable followed by Poshilo Makai-1 as compare to Farmer’s variety. The overall higher mean grain yield and regression coefficient (b) near to unity showed that S99TLYQ-HG-B is the most adaptive genotype across the tested environments. However, more than unity regression coefficient (b) indicates that Poshilo Makai-1 could be the recommended variety for better environments under farmers’ management.